A rapid, sensitive, and reproducible in vivo PBMC humanized murine model for determining therapeutic‐related cytokine release syndrome. Issue 9 (9th August 2020) - Ye, Chunting; Yang, Hongyuan; Cheng, Mingshan; Shultz, Leonard D.; Greiner, Dale L.; Brehm, Michael A.; Keck, James G.
Abstract: Immunotherapy is a powerful treatment strategy being applied to cancer, autoimmune diseases, allergies, and transplantation. Although therapeutic monoclonal antibodies (mAbs) have demonstrated significant clinical efficacy, there is also the potential for severe adverse events, including cytokine release syndrome (CRS). CRS is characterized by the rapid production of inflammatory cytokines following delivery of therapy, with symptoms ranging from mild fever to life‐threating pathology and multi‐organ failure. Overall there is a paucity of models to reliably and accurately predict the induction of CRS by immune therapeutics. Here, we describe the development of a humanized mouse model based on the NOD‐ scid IL2rg null (NSG) mouse to study CRS in vivo. PBMC‐engrafted NSG, NSG‐MHC‐DKO, and NSG‐SGM3 mice were used to study cytokine release in response to treatment with mAb immunotherapies. Our data show that therapeutic‐stimulated cytokine release in these PBMC‐based NSG models captures the variation in cytokine release between individual donors, is drug dependent, occurs in the absence of acute xeno‐GVHD, highlighting the specificity of the assay, and shows a robust response following treatment with a TGN1412 analog, a CD28 superagonist. Overall our results demonstrate that PBMC‐engrafted NSG models are rapid, sensitive, and reproducible platforms to screen novel therapeutics for CRS.